The Fly River : A Continuing Hydrographic Challenge - Done, P. (The International Hydrographic Review, 2015)
The importance of the Ok Tedi scheme of the Fly River in Papua New Guinea (PNG) is emphasized. The navigational and hydrographic problems connected with this waterway are discussed.